Participation rates and representativeness of African Americans recruited to a health promotion program - Halbert, Chanita Hughes (Oxford University Press, 2010)
When using community-based participatory methods to develop health promotion programs for specific communities, it is important to determine if participation differs based on sociodemographics and the extent to which program participants are demographically representative of the target community, especially when non-random recruitment methods are used. We evaluated rates of participating in a health promotion program among African American residents in an urban community and determined if program participants were representative of community residents in terms of sociodemographic factors. While participation in the program was modest, participation did not differ based on psychological factors or body mass index. However, individuals who were unemployed were significantly more likely to participate in the program compared with those who were employed. Our sample included a greater proportion of individuals who only had a high school education compared with community residents but was similar to community residents in terms of gender, marital status and employment.